Type 1 Tympanoplasty by Interlay Technique for Management of Tympanic Membrane Perforation - Biswas, Binoy Krishna; Khan, Manjurul Karim; Gupta, Subir (Community Based Medical Journal, 2023)
Tympanic membrane is the partition between the external ear and middle layer which is a vital component of the human ear. Neglected or maltreated earache, ear discharge and trauma lead to perforation of tympanic membrane. Tympanoplasty is the surgical procedure performed to repair a perforated tympanic membrane, with/without reconstruction of the ossicles, with the aim of preventing reinfection and restoring hearing ability. Type 1 tympanoplasty is the simple closure of the tympanic membrane perforation. To study the outcome of type 1 tympanoplasty operation by interlay technique, a descriptive longitudinal study was conducted among 200 patients in Community Based Medical College Hospital and in private clinics of Mymensingh from January 2012 to December 2021. Our inclusion criteria was population of age ranging from 15 to 55 yrs of both sexes having dry central perforation for at least 6 weeks and exclusion criteria was patient with active stage of chronic suppurative otitis media (CSOM), ossicular discontinuity, sensory neural hearing loss. Data was analyzed by SPSS version 20.0. Prevalence of taking graft was 96.00%. Measured by difference of preoperative air bone gap (ABG) and postoperative ABG of 15 decibel (dB) hearing improvement rate was 90%. Complication was minimal (1%). The complication was infection due to non-compliance with postoperative advice and treatment. Type 1 tympanoplasty done by interlay technique has excellent results both in terms of graft taken and hearing improvement with minimal complications. CBMJ 2023 January: Vol. 12 No. 01 P: 67-72